Rainwater harvesting technology to increase cropping index under perennial crops. Issue 1 (February 2021) - Heryani, N; Kartiwa, B; Hamdani, A; Muhardiono, I; Rahayu, B; Purwaningasih,
Abstract: Spatial and temporal water availability uncertainties are the major constraints to dryland crops productivity. Comprehensive hydrologic survey to determine water harvesting location as supplementary irrigation source is the key to increase dryland cropping index. This research was conducted in Lampung during April to December 2019. The aims of this research were to develop water management designs and irrigation techniques for upland rice and maize cultivation under perennial crops. The applied irrigation techniques consisted of sprinkler, furrow, and hose spray, while 3 varieties of the used upland rice were Rindang 1, Rindang 2, and Inpago 10. Results of this research revealed differences in crop productivity between paddy under " sengon " and rubber. This finding suggests supplement irrigation requirement from water harvesting infrastructures to increase land productivity during dry season. Moreover, the percentage of tolerable shading was up to 50% or 3 year age of the perennial crops.